VD_FINDINFO Décision / 2017 / 529 vom 13. Juni 2017 - VD Tribunal cantonal (2017)
CLASSEMENT DE LA PROCÉDURE, CONTRAINTEDROIT PÉNAL, DÉCISION SUR FRAIS | 181 CP, 382 al. 1 CPP (CH), 429 al. 1 let. a CPP (CH)